Integration of Deep Learning in AI-Based Learning to Improve Primary School Teachers’ Digital Literacy: Integrasi Deep Learning dalam Pembelajaran Berbasis AI untuk Meningkatkan Literasi Digital Guru Sekolah Dasar - Heryon Bernard Mbuik; Hingrida Margarita Anastasia Hendrik Anastasia Hendrik; Musa Daniel Nakmofa (Lembaga Riset dan Inovasi Masyarakat Madani, 2026)
This community service (PKM) program addresses the need to strengthen digital literacy and pedagogically grounded artificial intelligence (AI) integration among primary school teachers. The program implemented a practice-based training model combined with a co-design pedagogy approach, enabling teachers to actively engage as learning designers rather than passive technology users. The activity was conducted at SDN Oetona, Kupang, involving twelve primary school teachers. Evaluations were carried out through pre- and post-tests, observation of instructional practices, and guided reflective responses. The findings indicate a notable improvement in teachers’ conceptual understanding, operational readiness, and confidence in integrating AI into lesson planning and classroom activities, with 80% of participants demonstrating the ability to apply basic AI tools for instructional support. Despite positive outcomes, the program faced limitations related to training duration, participant scale, and device availability. As a follow-up strategy, a school-based learning community was established to support sustained collaboration, mentoring, and the gradual development of AI-supported pedagogical practices in primary education.